2014
DOI: 10.1007/s11665-014-0936-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pin Length on Hook Size and Joint Properties in Friction Stir Lap Welding of 7B04 Aluminum Alloy

Abstract: Friction stir lap welding of 7B04 aluminum alloy was conducted in the present paper, and the effect of pin length on hook size and joint properties was investigated in detail. It is found that for each given set of process parameters, the size of hook defect on the advancing side shows an ''M'' type evolution trend as the pin length is increased. The affecting characteristics of pin length on joint properties are dependent on the heat input levels. When the heat input is low, the fracture strength is firstly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…In Yadava et al's research [6], the load-carrying ability of lap joints was found to be linearly decreased with the increase of the height of the hook defect, indicating that the height of the hook defect had remarkable influence on the joint properties. A similar phenomenon was also observed in our previous study on FSLW of 7B04 aluminum alloy where the large height of the hook defect would lead to the poor tensile properties of the joints [9]. Nevertheless, Yazdanian et al [7] suggested that for the FSLW of 3-mm-thick 6060-T5 aluminum alloy, the strength reduction due to the hook defect only became significant when the height of the hook defect reached a critical value of ~0.9 mm.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In Yadava et al's research [6], the load-carrying ability of lap joints was found to be linearly decreased with the increase of the height of the hook defect, indicating that the height of the hook defect had remarkable influence on the joint properties. A similar phenomenon was also observed in our previous study on FSLW of 7B04 aluminum alloy where the large height of the hook defect would lead to the poor tensile properties of the joints [9]. Nevertheless, Yazdanian et al [7] suggested that for the FSLW of 3-mm-thick 6060-T5 aluminum alloy, the strength reduction due to the hook defect only became significant when the height of the hook defect reached a critical value of ~0.9 mm.…”
Section: Introductionsupporting
confidence: 84%
“…The tool pin had a diameter of 4.5 mm (at the shoulder) and a pin length of 2.8 mm. Note that the pin length of the welding tool is the optimal result of our previous work [9]. During the welding, an axial load of 4.6 kN and a tilting angle of 2.5˝were applied to the welding tool.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Song et al (2014) considered that the pin tool penetrated into the lower sheet to a certain depth to generate a bonding region resulting in original interfaces extruding upwards in the SZ. Wang et al (2014) suggested that the material around pin tool underwent circular and upward flow due to the shearing of threads leading to the formation of interface defects. In order to optimize the FSLW process, it is of great interests and importance to investigate the formation mechanism of the interface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Xing [6,7] demonstrated that the height of interface migration increased with the increase of plunge depth of shoulder and interface migration of the retreating side was higher than the advancing side in FSLW joint of aluminum alloy. Wang et al [8] discussed the influence of the length of the needle on hook type size and joint performance. Al-badour et al [9] established a finite element model to simulate dissimilar alloy FSLW of different mixing needle.…”
Section: Introductionmentioning
confidence: 99%